Differentiating strategies for transition to the new economy : Hong Kong & Singapore vs. South Korea & Taiwan. - Lee, Karen Huay Ying. (2008)
Discussed the differentiating strategies for transition to the new economy: Hong Kong & Singapore vs. South Korea & Taiwan.